Efficacy and Safety of Topiramate as Monotherapy in Treatment of Partial Epilepsy in Children: A Randomized Controlled Trial (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Partial epilepsy is more common among children.Objective: The aim of the study was to compare the efficacy and safety of Topiramate (TPM) to previously recommended drug Carbamazepine (CBZ) in the treatment of partial epilepsy.Methodology: This randomized controlled trial was conducted in outpatient department of Pediatric Neurology at National Institute of Neurosciences and Hospital (NINS&H), Dhaka, Bangladesh during the period of July 2017 to December 2017. Children with the age group of 0 to 18 years who were diagnosed as newly onset partial epilepsy were randomized into study group (TPM) and control group (CBZ). The efficacy and safety of TPM was evaluated after 6 months of treatment.Results: A total number of 50 children were recruited for this study. The primary outcome was assessed in 50 children by measuring frequency of seizure before and after treatment. Seizure frequency decrease significantly after treatment with both drugs where TPM group was 5.21±2.96 to 1.80±0.94 and CBZ group was 6.83±4.88 to 1.80±1.0/month respectively (p